Exploring the early Universe with Gaia and Theia. Issue 12 (10th December 2021) - Garcia-Bellido, Juan; Murayama, Hitoshi; White, Graham
Abstract: It has recently been pointed out that Gaia is capable of detecting a stochastic gravitational wave background in the sensitivity band between the frequency of pulsar timing arrays and LISA. We argue that Gaia and Theia have great potential for early universe cosmology, since such a frequency range is ideal for probing phase transitions in asymmetric dark matter, SIMP and the cosmological QCD transition. Furthermore, there is the potential for detecting primordial black holes in the solar mass range produced during such an early universe transition and distinguish them from those expected from the QCD epoch. Finally, we discuss the potential for Gaia and Theia to probe topological defects and the ability of Gaia to potentially shed light on the recent NANOGrav results.